2004
DOI: 10.1088/0031-9155/49/17/002
|View full text |Cite
|
Sign up to set email alerts
|

Linear energy transfer dependence of a normoxic polymer gel dosimeter investigated using proton beam absorbed dose measurements

Abstract: Three-dimensional dosimetry with good spatial resolution can be performed using polymer gel dosimetry, which has been investigated for dosimetry of different types of particles. However, there are only sparse data concerning the influence of the linear energy transfer (LET) properties of the radiation on the gel absorbed dose response. The purpose of this study was to investigate possible LET dependence for a polymer gel dosimeter using proton beam absorbed dose measurements. Polymer gel containing the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 23 publications
3
56
0
Order By: Relevance
“…gamma ray inflicts damages mostly indirectly through producing free radicals, while neutron, in contrast, produces alpha particles, recoil protons and heavier nuclear fragments, inflicting 12 | P a g e damages directly (Hall and Giaccia, 2012). In this study, the observed low gel sensitivity in thermal neutron irradiation is in accordance with the results of studies were conducted to employ polymer gels for measuring dose resulting from high LET particles such as proton and heavy ions (Gustavsson et al, 2004;Heufelder et al, 2003;Jirasek and Duzenli, 2002;Ramm et al, 2000). In these studies, it was found that the gel sensitivity for high LET particles is significantly smaller than high-energy photons, and the gel sensitivity decreases as radiation LET increases.…”
Section: Gamma Irradiationsupporting
confidence: 87%
“…gamma ray inflicts damages mostly indirectly through producing free radicals, while neutron, in contrast, produces alpha particles, recoil protons and heavier nuclear fragments, inflicting 12 | P a g e damages directly (Hall and Giaccia, 2012). In this study, the observed low gel sensitivity in thermal neutron irradiation is in accordance with the results of studies were conducted to employ polymer gels for measuring dose resulting from high LET particles such as proton and heavy ions (Gustavsson et al, 2004;Heufelder et al, 2003;Jirasek and Duzenli, 2002;Ramm et al, 2000). In these studies, it was found that the gel sensitivity for high LET particles is significantly smaller than high-energy photons, and the gel sensitivity decreases as radiation LET increases.…”
Section: Gamma Irradiationsupporting
confidence: 87%
“…This finding contradicts our previous results, which showed a decrease in the dose– response of polymer gel to high‐LET radiation. The BANG‐1‐type polymer gel has been reported to underestimate the absorbed dose at the Bragg peak of the proton beam by 20%30% ( 4 , 5 , 11 ) and by 10%40% at carbon ion beams of various energies (6) . The BANG‐3‐type gels underestimate dose under the same conditions by 50% and 40%60% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The BANG‐3‐type gels underestimate dose under the same conditions by 50% and 40%60% respectively. ( 4 6 , 11 ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] However, the dynamic nature of IMPT as well as the necessity to use thousands of scanning proton beamlets makes treatment verification both time consuming and difficult to perform. [7][8][9][10][11] We have previously studied the feasibility of using a three-dimensional liquid scintillator (LS) detector system to rapidly verify proton treatments. 12,13 Using a tank of LS and a high sensitivity CCD camera, we have shown that monitoring the passage of a proton beam is feasible.…”
Section: Introductionmentioning
confidence: 99%